Cultos, ferias y asambleas: los santuarios protohistóricos del Rin Medio-Mosela como espacios de agregación (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The construction of collective identities through sanctuaries ,is a key element for the understanding of protohistoric societies and in par- ticular of their dynamics of aggregation. This article analyses the subject, taking the territory of the Gallic ethnic group of the Treveri as a starting point. Research in the last two decades has revealed abundant references to the existence of public spaces/sanctuaries inside their oppida. In a subse- quent step, this view is expanded through theoretical reflections and exam- ples from both Gaul and other parts of the Ancient and Early Medieval world. Finally, a renewed approach to the genesis of oppida in températe Europe is proposed, which can also serve as an incentive for a re-evaluation of the subject in other areas such as the Iberian Peninsula.
Keywords: Sanctuaries; Fairs; Assemblies; Treveri; Oppida